2019
DOI: 10.1155/2019/1463896
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Reflux Is a Potential Risk Factor for Juvenile-Onset Recurrent Respiratory Papillomatosis

Abstract: Introduction. Human papillomavirus (HPV) causes juvenile-onset recurrent respiratory papillomatosis (JORRP). Although HPV is common in children, the prevalence of JORRP is low. It is likely that other factors contribute to the pathogenesis of JORRP, during either activation or reactivation of a latent HPV infection. There is evidence that laryngopharyngeal reflux (LPR) might be such a risk factor for adult-onset recurrent respiratory papillomatosis. This study investigated if LPR might also be a risk factor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
0
18
0
3
Order By: Relevance
“…87 Pepsin has been detected inside the mucosal cell cytoplasm of 45.5% of children with RRP, suggesting that laryngopharyngeal reflux may be a risk factor for JoRRP, contributing to its development by activating or reactivating latent HPV infection. 88 Patients with clinical features suggestive of GERD should therefore be treated with a H2-antagonist or proton pump inhibitor. 56 Of the three currently available HPV vaccines, the bivalent vaccine (Cervarix ® ), quadrivalent vaccine (Gardasil ® ), and nonavalent vaccine (Gardasil ® 9), two (Gardasil ® and Gardasil ® 9) protect against HPV6 and HPV11.…”
Section: Disease Coursementioning
confidence: 99%
“…87 Pepsin has been detected inside the mucosal cell cytoplasm of 45.5% of children with RRP, suggesting that laryngopharyngeal reflux may be a risk factor for JoRRP, contributing to its development by activating or reactivating latent HPV infection. 88 Patients with clinical features suggestive of GERD should therefore be treated with a H2-antagonist or proton pump inhibitor. 56 Of the three currently available HPV vaccines, the bivalent vaccine (Cervarix ® ), quadrivalent vaccine (Gardasil ® ), and nonavalent vaccine (Gardasil ® 9), two (Gardasil ® and Gardasil ® 9) protect against HPV6 and HPV11.…”
Section: Disease Coursementioning
confidence: 99%
“…From these, 64 were related to VF granuloma, 129 to laryngotracheal stenosis, 100 to laryngeal infections, and 48 to leukoplakia. Among these articles, 31 met our inclusion criteria and were kept for analysis ( Figure 1 ): 8 related to VF granuloma ( Table 1 ), 20-27 4 to laryngeal infections ( Table 1 ), 28-31 5 to leukoplakia ( Table 2 ), 7,32-35 and 10 to laryngotracheal stenosis ( Table 3 ). 36-45 Four additional basic research studies were identified concerning the relationship between reflux and the development of laryngotracheal stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies focused on the relationship between LPR and chronic laryngeal infections—namely, laryngeal papillomatosis 28,30,31 and methicillin-resistant Staphylococcus aureus (MRSA). 29 The papillomatosis articles are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations